2013
DOI: 10.3346/jkms.2013.28.12.1774
|View full text |Cite
|
Sign up to set email alerts
|

Change in Somatostatinergic Tone of Acromegalic Patients according to the Size of Growth Hormone-Producing Pituitary Tumors

Abstract: The aim of this study was to investigate the relationship between somatostatinergic tone (SST) and the size of growth hormone (GH)-producing pituitary tumors. GH levels of 29 patients with newly diagnosed acromegaly were measured using a 75-gram oral glucose tolerance test (OGTT), an insulin tolerance test (ITT), and an octreotide suppression test (OST). Differences between GH levels during the ITT and the OGTT (ΔGHIO), and between the OGTT and the OST at the same time point (ΔGHOS) were compared according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Therefore, the presence of this mutation may not be sufficient to explain the relationship between responsiveness of GH to TRH and tumor volume. We previously reported that as the tumor becomes larger, there exists a portion of the GH secretion which escaped physiologic regulation by somatostatinergic tone (SST) [ 25 ]. One of the known hypotheses for the paradoxical response in GH to TRH administration is the inhibition of somatostatin release by TRH [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the presence of this mutation may not be sufficient to explain the relationship between responsiveness of GH to TRH and tumor volume. We previously reported that as the tumor becomes larger, there exists a portion of the GH secretion which escaped physiologic regulation by somatostatinergic tone (SST) [ 25 ]. One of the known hypotheses for the paradoxical response in GH to TRH administration is the inhibition of somatostatin release by TRH [ 13 ].…”
Section: Discussionmentioning
confidence: 99%